USE OF BENTONITE-CHITOSAN MIXTURE AS AN AMMONIUM SULFATE CARRIER IN MANUFACTURING SLOW RELEASE FERTILIZER: - - Tobing, Marta; Suarya, P.; Prayikaputri, P. U (Jurnal Ilmu Pendidikan Indonesia, 2024)
Nitrogen is a nutrient that is needed for the process plant growth, but nitrogen is easily carried away by water and evaporates, it causes farmers to fertilize excessively. This cause environmental pollution. The aim of this research is to make slow release fertilizer (SRF) with a bentonite-chitosan-ammonium sulfate formula to increase fertilization efficiency. Mixing was using the liquid-liquid method where 50 mL of 20% (NH4)SO4 was mixed with 20% bentonite-1% chitosan in a ratio of 10:0; 10:20; 20:20; 30:20; 40:20; 50:20. The highest total nitrogen content was obtained in SRF with a bentonite-chitosan ratio of 0:50 (3.94%) which was tested using the Kjeldahl method. Comparison of release tests on SRF and pure fertilizer was carried out every day for 6 days, SRF increased slowly, namely from 0.07%; 0.18%; 0.27%; 0.6%; 0.42%; 0.5%while in 20% (NH4)SO4 fertilizer there was a release of 0.07%; 0.18%; 0.27%; 0.6%; 0.42%; 0.5%%. Nitrogen release in SRF is slower than in ammonium sulfate fertilizer